K. W. Harrow (Ed.). (2017). African filmmaking: Five formations. East Lansing, MI: Michigan State University Press. 301 pp. - L. Rosenberg, Aaron (Estudios de Asia y África, 2019)
K. W. Harrow (Ed.). (2017). African filmmaking: Five formations. East Lansing, MI: Michigan State University Press. 301 pp.